Analytic Ecclesiology: The Paradox of the Unity of the Church - Devina Benlin Oswan (Veritas : Jurnal Teologi dan Pelayanan, 2022)
Analytic Ecclesiology is a new branch within the enterprise of Analytic Theology. The “analytic” part of the name refers to the analytic method employed to explicate the core claims of Christian theology using the tools of analytic philosophy. In the case of Ecclesiology, the concept of ecclesiastical unity demands clarification. The question is not why or how a collection of individuals is united but in what sense they are one. The Scriptural answer to the former is that Christ is the head of the Church. It is the latter that Analytic Ecclesiology is committed to answering. Joshua Cockayne’s work, which focuses on the social ontology and group agency of the Church, has shed some light on the issue. He invites philosophers and theologians in the analytic tradition to think about Ecclesiology analytically. That is my aim in this paper. I hope to expand the discussion on Analytic Ecclesiology, not by building on Cockayne’s work, but rather by taking a step back and arguing that the issue of the unity of the Church must be discussed from the perspective of identity rather than, contra Cockayne, from the perspective of group agency. To achieve this, I shall first assess Cockayne’s account and offer my criticism. Then, drawing insights from Peter Unger’s article “Problem of the Many,” I discuss the paradox of the unity of the Church and conclude that relative identity theory best solves the paradox of the unity of the Church.